Pendidikan Nonformal dalam Kerangka Revitalisasi Nasionalisme Bangsa di Tengah Kompleksitas Fragmentasi Identitas Global Kontemporer - Istighfari, Masayu Kyla; Habibah, Siti Maizul Habibah (Journal of Civics and Moral Studies, 2025)
Globalization and the advancement of information technology have significantly transformed the lives of Indonesian people. This transformation not only broadens access to the outside world but also changes social values and identities, potentially weakening the sense of nationalism. The younger generation is now largely exposed to global cultures that tend to shift national and local values. This study aims to analyze the role of nonformal education in strengthening nationalism amid identity fragmentation caused by globalization. The research method employs a literature study approach involving scientific articles, government policies, and recent studies since 2020. The results show that nonformal education has great potential to rebuild the spirit of nationalism through community-based, culturally rooted, and socially participatory activities. Institutions such as Community Learning Centers, art studios, and youth organizations have proven to be spaces for strengthening national identity through contextual and reflective learning. Nonformal education also serves as a vehicle for character formation that aligns with contemporary dynamics. This study recommends that the government reinforce policies that integrate national values into every nonformal education program in Indonesia.